INTEGRASI NILAI-NILAI MULTIKULTURAL DALAM SISTEM PENDIDIKAN DI PONDOK PESANTREN NURUL UMMAH KOTAGEDE - Aminul Qodat (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2019)
This research is motivated by misunderstanding in the attitude of pluralism that still leaves many problems. So students often gain Knowledge about religion which is based on exclusivism, Consequently the seeds of conflict continue to be embedded in religious experience and cognition of religion which is believed by students, in turn often become trigger of violence over The name of religion. Pesantren which is included in the national education system is an Islamic educational institution, which has a task to transform and integrate the values humanist, democratic, peaceful and tolerant in the life of santri in pesantren. The phenomenon makes the researcher to study how the integration of multicultural values ​​in the education system of Pesantren Nurul Ummah Kotagede Yogyakarta. The results of the research concluded that: Integration of Multicultural Values ​​in Education System Pondok Pesantren Nurul Ummah Kotaged. Through the aspects, Curriculum Planning Education Madrasah Diniyah, Learning activities, examples of Educators, and Evaluation Education. Although there is no material and field Special studies related to Multicultural in pesantren, but Multicultural Values ​​have been integrated in various forms of daily activities both in the context of the pesantren environment and outside the pesantren, in the form of an unwritten curriculum or hidden curriculum. With found the existence of Humanist Democracy Value in the Pesantren Program, the Value of Justice in the Regulation, Equality Value in the Placement of students, and the Value of Togetherness, Tolerance and Value of Peace in the culture of Santri. So Multicultural Value is considered a form of respect for diversity and recognition pedagogical equilibrium a person who has the same right to obtain educational services, regardless of ethnicity, social status, language and type of education level.